Superannuation: don’t kill the goose that lays the golden egg - Pinto, Dale (Taxation Institute of Australia, 2013)
The taxation of superannuation arrangements in Australia has undergone many changes, particularly since 1983. In the lead-up to the federal Budget in May 2013 and the federal election in September 2013, there are rumours of further changes to come. This article examines some of the policy considerations underlying changes which may be considered by the government. The article considers the policy context, the place of superannuation as a component of household wealth, the fiscal context, superannuation as a ‘cash cow’ for government, and the tax expenditures argument. The author argues against any further changes being made to the superannuation rules and presents reasons which support this position.